2018
DOI: 10.1108/bpmj-02-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Propositions on the interaction of organizational culture with other factors in the context of BPM adoption

Abstract: Purpose The paper investigates differences in the success of business process management (BPM) initiatives and their connection with organizational culture. The purpose of this paper is to identify propositions on characteristics of BPM initiative that are favorable for its success according to dominant organizational culture. Therefore, the authors’ aim was to identify connections of organizational commitment to BPM and dimensions of business process orientation (BPO) with dominant organizational culture. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
0
14
0
3
Order By: Relevance
“…Article [22] The reasons for which academics quit jobs, in the context of the impact of leadership, organizational commitment and organizational culture are examined. It is concluded that the leaders should recognize the leadership impact, as leaders' behavior can motivate the commitment of higher school employees and reduce the turnover intentions Article [23] Organizational Culture…”
Section: Thematic Changes In the Spectrum Of Research On Organizationmentioning
confidence: 99%
“…Article [22] The reasons for which academics quit jobs, in the context of the impact of leadership, organizational commitment and organizational culture are examined. It is concluded that the leaders should recognize the leadership impact, as leaders' behavior can motivate the commitment of higher school employees and reduce the turnover intentions Article [23] Organizational Culture…”
Section: Thematic Changes In the Spectrum Of Research On Organizationmentioning
confidence: 99%
“…Ambas perspectivas matizan la forma de abordar los diferentes niveles de abstracción del paradigma BPM como el ciclo BPM y las particularidades de sus fases, la adopción de determinados estándares propios del paradigma [9] y el modelado de procesos de negocio [10]. En este sentido, los procesos de adopción de iniciativas BPM que impliquen el desarrollo de soluciones TI guiadas por este paradigma enfrentan complejidades tales como: orientación a procesos [11][12], la cultura organizacional [13], la competencias y capacitación en el dominio BPM [14][15] y el seguimiento de una metodología, procedimiento o buenas prácticas para el desarrollo de soluciones BPM [16].…”
Section: Introductionunclassified
“…The sustainable development of any organization is closely related to the culture of that organization [1][2][3]. Employees like to work in professional environments which resonate with their own values [4].…”
Section: Introductionmentioning
confidence: 99%
“…Organizational culture is an important concept in the field of management [1,2,[6][7][8][9]. The interest for this concept was first developed in the private sector, but public institutions gradually discovered for themselves the value of this notion.…”
Section: Introductionmentioning
confidence: 99%